Macro- and Micro-Nutrient Composition and Antioxidant Activity of Chickpea and Pea Accessions - Michela Costantini; Carmine Summo; Mariangela Centrone; Iga Rybicka; Mariagrazia D’Agostino; Paolo Annicchiarico; Francesco Caponio; Stefano Pavan; Grazia Tamma; Antonella Pasqualone (Polish Journal of Food and Nutrition Sciences)
Epidemiological studies reported an inverse association between the consumption of legumes and the incidence of age-related diseases. This trend could be attributed to the presence of antioxidant compounds, especially phenolic and flavonoid compounds. In this paper, five pea ( Pisum sativum L.) and twelve chickpea ( Cicer arietinum L.) accessions, having different characteristics and geographical origin, were characterised in terms of antioxidant activity, as well as macro- and micro-nutrient composition. The antioxidant activity has been evaluated using both DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) radical scavenging capacity assays. Chickpea and pea accessions showed a different behaviour in the presence of these different radicals. Chickpea accessions were characterised by significantly higher DPPH• scavenging activity, while peas showed a significantly higher value of antioxidant activity evaluated using the ABTS assay. Pea accessions had the highest content of total phenolic compounds, Zn, and Cu. A positive correlation was found between some minerals, such as Zn, Cu and P, and the ABTS •+ scavenging activity. Black and brown chickpea accessions showed significantly higher contents of anthocyanins, Mn, Mg, and Ca, which were positively correlated with the antioxidant activity assessed with the DPPH assay. Despite the dataset investigated in our study included a limited number of accessions, it was possible to highlight the influence of the chemical composition on the antioxidant activity due to the high phenotypic diversity found between the accessions, emphasising the importance of selecting the antioxidant activity assay according to the matrix to be evaluated.